Inhibition of Renin Angiotensin Axis May Be Associated with Reduced Risk of Developing Venous Thromboembolism in Patients with Atherosclerotic Disease - Chae, Young Kwang (Public Library of Science, 2014)
BACKGROUND: Arterial and venous thrombosis may share common pathophysiology involving the activation of platelets and inflammatory mediators. A growing body of evidence suggests prothrombotic effect of renin angiotensin system (RAS) including vascular inflammation and platelet activation. We hypothesized that the use of angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) plays a role in protecting against venous thromboembolism (VTE) in patients atherosclerosis. METHODS: We conducted a retrospective study, reviewing 1,100 consecutive patients admitted to a teaching hospital with a diagnosis of either myocardial infarction or ischemic stroke from 2005 to 2010. Patients who had been treated with anticoagulation therapy before or after the first visit were excluded. The occurrence of VTE during the follow up period, risk factors for VTE on admission, and the use of ACEIs or ARBs during the follow up period were recorded. RESULTS: The mean age of the entire study population was 68.1 years. 52.0% of the patients were female and 76.5% were African American. 67.3% were on RAS inhibitorsThe overall incidence of VTE was 9.7% (n = 107). Among the RAS inhibitor users, the incidence of VTE events was 9.0% (54/603) for the ACEI only users, 7.1% (8/113) for the ARB only users, and 0% (0/24) for the patients taking combination of ACEI and ARB. Among patients on RAS inhibitors, 8.4% (62/740) developed a VTE, compared with 12.5% (45/360) in the nonuser group [HR (hazard ratio), 0.58; 95% CI (confidence interval), 0.39–0.84; P<0.01]. Even after controlling for factors related to VTE (smoking, history of cancer, and immobilization, hormone use) and diabetes, the use of RAS inhibitors was still associated with a significantly lower risk of developing VTE (AHR, 0.59; 95% CI, 0.40–0.88; P = 0.01). CONCLUSIONS: The use of RAS inhibitors appears to be associated with a reduction in the risk of VTE.